The Population Dynamics and Parasitism Rates of Ceratitis capitata, Anastrepha fraterculus, and Drosophila suzukii in Non-Crop Hosts: Implications for the Management of Pest Fruit Flies - Buonocore Biancheri, María Josefina (2024)
Understanding the seasonal dynamics inherent to non-crop host–fruit fly–parasitoid interactions is vitally important for implementing eco-friendly pest control strategies. This study assessed the abundance and seasonal infestation levels of three pest fly species, Ceratitis capitata (Wiedemann), Anastrepha fraterculus (Wiedemann), Drosophila suzukii (Matsumura), as well as the related saprophytic drosophilids, and their natural parasitism in a disturbed wild habitat characterized by non-crop hosts in northwestern Argentina over 40 months. Juglans australis Griseb (walnut), Citrus aurantium L. (sour orange), Eriobotrya japonica (Thunb.) Lindley (loquat), Prunus persica (L.) Batsch (peach), and Psydium guajava L. (guava) were sampled throughout their fruiting seasons. Fruits were collected from both the tree canopies and the ground. The most abundant puparia was A. fraterculus, followed by C. capitata and D. suzukii. Drosophila species from the D. melanogaster group were highly abundant only in fallen fruits. Spatiotemporal overlaps of different host fruit availability provided suitable sources for pest proliferation throughout the year. The populations of both invasive pests peaked from December to January, and were related to the highest ripe peach availability, whereas the A. fraterculus population peaked from February to April, overlapping with the guava fruiting period. The three pest fly species were parasitized mainly by three generalist resident parasitoids, which are potential biocontrol agents to use within an integrated pest management approach.